A technical framework for determining water consumption thresholds in the semi-arid Xiliao River Plain based on terrestrial water balance - Xuanxuan Wang; Huan Liu; Yangwen Jia; Jianhua Wang; Xuewu Wei; Yuhua Wang; Xiaola Wang; Yefei Ji; Lei Dang; Peng Hu (Journal of Hydrology: Regional Studies)
Study regions: The Xiliao River Plain. Study focus: This study proposed a technical framework for determining water consumption thresholds in semi-arid regions based on terrestrial water balance. The technical framework includes three parts: adaptability evaluation and selection of remote sensing products, calculation of agricultural and ecological water consumption, and determination of water consumption thresholds. New hydrological insights for the region: This framework could separate agricultural and ecological water consumption, and effectively determining the water consumption thresholds. During the period of 1980–2022, agricultural water consumption increased significantly (p < 0.01) at the rate of 0.67 × 108 m3/year, but ecological water consumption decreased significantly (p < 0.05) at the rate of 0.20 × 108 m3/year. According to the type of major water-consuming sectors, the Xiliao River Plain was categorized into three types of regions: regions where agricultural water consumption accounted for the majority (AR), regions where ecological water consumption accounted for the majority (ER), and regions where agricultural and ecological water consumption together accounted for the majority (AER). For all three types of regions, a significant positive linear correlation between precipitation surplus coefficient and terrestrial water storage change was detected. To maintain terrestrial water balance, the proportion of total evapotranspiration consumption to precipitation should be limited to 76.3∼93.5 %. For AR, ER and AER, the proportion of major water-consuming sectors in precipitation should be controlled at 47.3∼63.1 %, 49.9∼62.7 % and 61.8∼80.0 %, respectively.